The possibility for a Civil Court to independently determine that a tort is a crime – comments in the light of case law of the European Court of Human Rights regarding presumption of innocence (Ius Novum, 2022)
According to the well-established Supreme Court’s case law, the civil court is entitled todetermine independently whether a tort constitutes a criminal offence even in the absenceof a final judgement of conviction. This opinion was expressed by the Supreme Court forthe purpose of applying the extended limitation period under Article 4421 § 2 of the CivilCode for claims for a tort that is a crime. The Supreme Court’s statement raises doubts on thegrounds of the presumption of innocence. The purpose of this article is firstly to present thestandard concerning the scope of the presumption of innocence in civil proceedings, createdby the European Court of Human Rights on the basis of Article 6 § 2 of the ECHR, accordingto which everyone charged with a criminal offence shall be presumed innocent until provedguilty according to law. Then it is the assessment of the compatibility of the Supreme Court’sopinion through the perspective of the Convention standard.
Keywords: presumption of innocence; the European Court of Human Rights; crime; tort; limitation for tort claims